Rare Sighting Record of Southern Duffer Discophora lepida Moore 1858 (Family Nymphalidae) in Nilgiris, Tamil Nadu, India - Moinudheen, N.; Samson, Arockiananathan; Sethumadhavan, Manoj; Sarathkumar, M. S.; Kumar, Clement Kishore (Journal of the Bombay Natural History Society (JBNHS), 2022)
No Abstract.